2022
DOI: 10.1097/as9.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act and its Effects on Trauma Care Access, Short- and Long-term Outcomes and Financial Impact

Abstract: Objective: The purpose of this study is to evaluate the current evidence regarding the impact of the ACA on trauma outcomes and the financial impact on trauma patients and trauma systems. Background: Traumatic injuries are the leading cause of death and disability between the ages of 1 to 47 years. Uninsured status has been associated with worse outcomes and higher financial strain. The Affordable Care Act (ACA) was signed into law with the aim of incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…One such change relevant to this study was the allocation of increased funding for trauma care centers in the form of federal grants and uncompensated care awards 46 . A 2022 meta-analysis found that the implementation of the ACA was associated with increased postacute care access but had limited effect on trauma mortality 47 . In their 2017 paper, Scott et al 48 estimated that the expanded insurance coverage offered by the ACA has the potential to increase national reimbursement for inpatient trauma care by more than $1 billion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such change relevant to this study was the allocation of increased funding for trauma care centers in the form of federal grants and uncompensated care awards 46 . A 2022 meta-analysis found that the implementation of the ACA was associated with increased postacute care access but had limited effect on trauma mortality 47 . In their 2017 paper, Scott et al 48 estimated that the expanded insurance coverage offered by the ACA has the potential to increase national reimbursement for inpatient trauma care by more than $1 billion.…”
Section: Discussionmentioning
confidence: 99%
“…46 A 2022 meta-analysis found that the implementation of the ACA was associated with increased postacute care access but had limited effect on trauma mortality. 47 In their 2017 paper, Scott et al 48 estimated that the expanded insurance coverage offered by the ACA has the potential to increase national reimbursement for inpatient trauma care by more than $1 billion. This finding suggests that ACA provisions may have afforded economic viability for the expansion of trauma care centers nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…At the main trauma hospital in Khon Kaen, Thailand, initiatives that increased staffing within their emergency department improved timely access to providers and helped reduce trauma mortality from 6.1% to 4.4% [ 27 ]. In the United States, the implementation of the Affordable Care Act reduced the number of uninsured Americans which has been found to be associated with greater access to trauma services and reduced financial risk [ 28 ]. In addition to accessing trauma centers, our panelists identified key resources, the presence of which signals an ability to provide adequate musculoskeletal trauma care.…”
Section: Discussionmentioning
confidence: 99%
“…While trauma bills following the ACA were universally found to have increased significantly, a proportionate increase in reimbursement for patient treatment was not consistently observed (although an increase having been observed in some trauma centers), with one review positing that provisions from the ACA were much less than previous allocations. 14 Another study noted that the population of uninsured patients rose sharply again in 2017, despite the ACA’s core tenets aimed at reducing this population. 15 Additional promises also remain to be upheld: the US$224 million allotment to trauma care and research by the ACA has yet to be distributed, and a subsequent effort in 2015 to pass the Trauma Systems and Regionalization of Emergency Care Reauthorization Act, which would allocate money from the Public Health Service Act, remains introduced but unvoted on by the Senate.…”
Section: Costsmentioning
confidence: 99%
“…This signals that while the ACA has provided tenable foundations to support disadvantaged patients and essential high designation trauma centers, additional care and funding are necessary to ensure tangibly improved outcomes. 14 Federal funding from other congressional appropriations, although present, is still insufficient to cover trauma center operating costs on its own and has consistently eroded, with federal offerings from the Trauma-Emergency Medical Services Systems Grant budget having decreased from US$4.8 million to US$2 million from 1996 to 2005. 18 …”
Section: Costsmentioning
confidence: 99%